Penerapan Metode Mind Mapping untuk Meningkatkan Keterampilan Menulis dalam Bahasa Inggris pada Fase A di SD Cita Hati Surabaya - Christian Siantar; Soegeng Wahyudi; Dwi Muwarni; Sarah Prasasti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research is action research that applies mind map to improve writing skill in English lesson for 2nd grade of Cita Hati Elementary School Surabaya. The subject of the research are 22 students of 2nd graders. The instruments are mind map worksheets to improve students’ writing skills in English lesson and the writing rubric adopted from Cambridge curriculum. This study is conducted in 2 cycles based on the Kemmis, McTaggart, Nixon’s theory (2014). Each cycle consists of 5 processes (planning, acting, observing, and reflecting, and re-planning). The first data in the pre-test shows that 11 students (50%) out of 22 students achieves the scores below minimum passing grade criteria. The writer continues to the processes of cycle 1 and it shows that 16 students out of 22 students who could achieve the minimum passing grade criteria so that the percentage becomes 73%. The writer does the 2nd cycle and it is found that all grade 2 students could achieve the minimum passing grade criteria and it improves the percentage into 100%. At the end of cycle 2, the writer could achieve the success indicator. Last but not least, this research stated that the use of mind map could improve the writing skill of 2nd grader in English lesson.